2010
DOI: 10.1038/ijo.2010.232
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and metabolic syndrome in Asian Indians

Abstract: In this study, we aimed to estimate serum 25-hydroxy vitamin D (25-OH-D) in Asian Indians and test for association between 25-OH-D levels, insulin resistance (IR) and metabolic syndrome (MS). Serum 25-OH-D was measured in a cross-sectional sample of 441 Indians, aged 39.7±12.8 years (237 men and 204 women) with 27.9% prevalence of MS. Vitamin D insufficiency (12.5 to o50 nmol l À1 ) and hypovitaminosis D (50 to o100 nmol l À1 ) were present in 65.6 and 31.1% of participants, respectively. The 25-OH-D levels di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 19 publications
(24 reference statements)
4
44
2
Order By: Relevance
“…However, our results are in agreement with a study that was conducted in Asian --Indian adults, which demonstrated a high prevalence of vitamin D insufficiency (25-OHD level o50 nmol l À1 ), but no association between vitamin D insufficiency and insulin resistance. 33 In contrast to the inverse relationship between plasma iPTH and insulin sensitivity demonstrated in a previous study, 34 our study did not find such a relationship. As the iPTH level has an inverse correlation with the 25-OHD level, the lack of an association between iPTH level and insulin sensitivity in our study may have been indirectly due to the lack of association between 25-OHD level and insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results are in agreement with a study that was conducted in Asian --Indian adults, which demonstrated a high prevalence of vitamin D insufficiency (25-OHD level o50 nmol l À1 ), but no association between vitamin D insufficiency and insulin resistance. 33 In contrast to the inverse relationship between plasma iPTH and insulin sensitivity demonstrated in a previous study, 34 our study did not find such a relationship. As the iPTH level has an inverse correlation with the 25-OHD level, the lack of an association between iPTH level and insulin sensitivity in our study may have been indirectly due to the lack of association between 25-OHD level and insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 99%
“…Like other studies our data also showed significant gender-specific differences. While some studies [25] show that males are at higher risk of MS as compared to females, our study like other studies in similar settings [24,26], showed higher (2.5 times) prevalence among females. Older subjects had higher odds of developing MS (Age> 46 had 1.9 times higher odds than Age≤46).…”
Section: Discussionsupporting
confidence: 58%
“…Studies have reported a prevalence of 70-100% of vitamin D deficiency in the Indian subcontinent [24,26] which is much higher than the prevalence range reported globally 30-50% [5,7,13]. There is a continued debate in the published literature with respect to the optimum cut-off for 25(OH) D. For the purpose of maintaining uniformity, we used the categories used in studies based in South Asia [17,18,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors demonstrated indifferent gender results in their studies with MS patients. 37,43 Our results can be explained by traditional clothing style of the women where our study was performed. It was found that in Turkish regions where women wore clothes with covered arms, Vit D levels were lower than the other parts of Turkey.…”
Section: Resultsmentioning
confidence: 82%